Anti-interference road lamp controller - MINXIN LIANG (2000)
The utility model relates to a road lamp control device. The utility model is composed of a brightness testing circuit, a controlling circuit, a time delay circuit, an output circuit, etc., wherein, the time delay circuit is composed of a counter, the counting pulse input terminal of which is connected with an oscillator. The control terminal of the counter is connected with the controlling circuit, and the output terminal of the counter is connected with the output circuit via a photoelectric isolating circuit. The input terminal of the controlling circuit is respectively connected with the brightness testing circuit and the output circuit. Compared with the prior art, the utility model has the advantages of reliable operation, strong anti-interference capability, etc.